Agronomic efficiency of triple superphosphate coated by polymers in the initial growth of the coffee (Coffee Science - ISSN 1984-3909, 2016)
The phosphate fertilizer in coffee has been widely discussed in recent years for research due to the problems facing the match reaction (P) in the culture of farming soils. Much of the set P is applied with iron and aluminum oxides, becoming unavailable to plants. One way to get around this problem is the use of slow or controlled release fertilizer that slowly release the nutrients to the soil solution. In order to find the agronomic efficiency and evaluate phytotechnical and nutritional characteristics such as height, dry weight of plants, leaf area, content and P accumulation in coffee leaves was carried out the experiment in a greenhouse at the Federal University of Lavras, in pots filled with 14 kg of soil and two coffee seedlings ‘Acaiá IAC 474-19’. The experiment design was randomized block arranged in a factorial 2x5 scheme. The treatments were constituted for two P sources (Triple superphosphate coated polymers and superphosphate conventional triple) and five doses of P2O5 (0, 5, 10, 15, 20 g vaso-1) by each of the sources, with four replicates. At the end of the experiment, we concluded that phosphate fertilizer influenced in all characteristics evaluated, where the phosphorus application promoted increase in coffee growth. The coating the fertilizer with polymers increased height, dry mass, phosphorus accumulation in coffee leaves and agronomic efficiency compared to conventional ST, being more efficient.